T cell immunity following COVID-19 vaccination in adult patients with primary antibody deficiency – a 22-month follow-up - Hurme, Antti; Jalkanen, Pinja; Marttila-Vaara, Minna; Heroum, Jemna; Jokinen, Heidi; Vara, Saimi; Liedes, Oona; Lempainen, Johanna; Melin, Merit; Julkunen, Ilkka; Kainulainen, Leena (Frontiers in Immunology, 2023)
Primary antibody deficiencies, such as common variable immunodeficiency (CVID), are heterogenous disease entities consisting of primary hypogammaglobulinemia and impaired antibody responses to vaccination and natural infection. CVID is the most common primary immunodeficiency in adults, presenting with recurrent bacterial infections, enteropathy, autoimmune disorders, interstitial lung diseases and increased risk of malignancies. Patients with CVID are recommended to be vaccinated against SARS-CoV-2, but there are relatively few studies investigating humoral and cellular responses to immunization. We studied the dynamics of humoral and cell-mediated immunity responses up to 22 months in 28 patients with primary immunodeficiency and three patients with secondary immunodeficiency receiving ChAdOx1, BNT162b2 and mRNA-1273 COVID-19 vaccines. Despite inadequate humoral response to immunization, we demonstrate a robust T cell activation likely protecting from severe COVID-19.